Determinants of the Income Strategy of Publicly Listed Corporations in the Philippines - Banse, Jessa Mae S. (Animo Repository, 2020)
The motivation of managers in selecting accounting policy is believed to be beyond the method’s simplicity, ease of implementation, and cost-benefit tradeoff to manage earnings by influencing the treatment of financial information. Anchored on positive accounting theory (PAT), this study examines the factors that influence the managers of 60 publicly listed companies in their choice of accounting methods when used as an income strategy. Specifically, this study evaluates whether efficient contracting, political sensitivity, need for financing, information signaling, investment opportunity set (IOS), and monitoring mechanisms (i.e., ownership concentration, board composition, and external auditor) influence the income strategy of management. Income strategy is based on the portfolio of accounting policies on inventory valuation, subsequent measurement of depreciable PPE, land, investment property, software, and depreciation method. Using partial least square structural equations modeling (PLS-SEM), this study found a significant negative relationship between efficient contracting and income strategy and positive relationship between ownership concentration and income strategy, which suggest the alignment of interests between shareholders and management. Political sensitivity is also found to be negatively significant, which validates that executives of Philippine companies choose income-decreasing policies to reduce the perceived size and resources of the company and eventually avoid government interventions and actions from a labor union.